2017
DOI: 10.1038/s41598-017-13699-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Cyclability of Substoichiometric Silicon Nitride Thin Film Anodes for Li-ion Batteries

Abstract: Silicon has been the subject of an extensive research effort aimed at developing new anode materials for lithium ion batteries due to its large specific and volumetric capacity. However, commercial use is limited by a number of degradation problems, many of which are related to the large volume change the material undergoes during cycling in combination with limited lithium-diffusivity. Silicon rich silicon oxides (SiOx), which converts into active silicon and inactive lithium oxide during the initial lithiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…32 have reported that 200 nm and 500 nm SiN 0.92 thin films exhibited first cycle reversible capacities of approximately 1,500 mAh/g and 1,000 mAh/g, and retained capacities of 1,300 mAh/g and 700 mAh/g after 100 cycles, respectively. Similar thin films of a-SiN 0.89 have also been found to exhibit a comparable reversible capacity of more than 1250 mAh/g 33 over 2400 cycles. In these works, silicon nitride is assumed to function as a conversion material, forming active silicon and an inactive nitride matrix component 31 33 .…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…32 have reported that 200 nm and 500 nm SiN 0.92 thin films exhibited first cycle reversible capacities of approximately 1,500 mAh/g and 1,000 mAh/g, and retained capacities of 1,300 mAh/g and 700 mAh/g after 100 cycles, respectively. Similar thin films of a-SiN 0.89 have also been found to exhibit a comparable reversible capacity of more than 1250 mAh/g 33 over 2400 cycles. In these works, silicon nitride is assumed to function as a conversion material, forming active silicon and an inactive nitride matrix component 31 33 .…”
Section: Introductionmentioning
confidence: 78%
“…Similar thin films of a-SiN 0.89 have also been found to exhibit a comparable reversible capacity of more than 1250 mAh/g 33 over 2400 cycles. In these works, silicon nitride is assumed to function as a conversion material, forming active silicon and an inactive nitride matrix component 31 33 . The exact nature of the matrix has not yet been determined, but it has been suggested to consist of Si 3 N 4 and/or Li 3 N 30 , 31 , or a ternary lithium silicon nitride, e.g.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Silicon nitride films are useful in microelectronics applications [1] such as oxidation masks, protection and passivation barrier layers, gate dielectrics and interlevel insulations due their remarkable hardness, high thermal stability, chemical inertness and excellent insulation capabilities [2]. These films also play important role in optoelectronic applications such as antireflection coatings and optimization of optical performance of devices due to its capability of providing the refractive index variation from silicon oxide like (~1.46) to stochiometric silicon nitride (~2.0) and by providing transparency in ultraviolet (250nm) to infrared (9µm) regions of optical spectrum [3].…”
Section: Introductionmentioning
confidence: 99%